(untitled) (Bangladesh Journal of Zoology, 2018)
Rodents are regarded as crop pests, significant reservoirs and vectors for many zoonotic diseases around the world. Basic taxonomic information of rodents present in a locality can help understand which species are responsible as crop pest in that habitat. The phenomenon of the 50-year cycle of gregarious bamboo flowering and rodent outbreaks in the Chittagong Hill Tracts (CHT) of Bangladesh, rodents trapping were carried out in four habitats from March, 2009 to December, 2011 in Ruma upazila of Bandarban hill district. Variety of traps were used to capture small mammals. The captured species were measured and identified using taxonomical dichotomous keys and DNA bar-coding performed in Australia. A total of 14 different small mammalian species were captured of which nine belonging to the Muridae family, and one species each of Spalacidae, Sciuridae, Tupaiidae and Soricidae families. The dominant small mammal species captured were Rattus rattus (54.06%) followed by Mus musculus (26.39%), Rattus nitidus (10.98%), Suncus murinus (5.45%), Mus terricolor (1.09%), Mus cookii nagarum (0.97%), Cannomys badius (0.16%), Leopoldamys edwardsi (0.12%), Berylmys bowersi (0.12%), Vernaya fulva (0.08%), Rattus andamanensis (0.08%), Tupaia glis (0.04%) and Callosciurus pygerythrus (0.04%). Rattus nitidus, Leopoldamys edwardsi, Vernaya fulva, Rattus andamanensis, Berylmys bowersi and Mus cookii nagarum are new records of rodent species in Bangladesh. Ten individuals of Mus spp. (0.40%) were not identified to species level, requiring further genetic analysis to determine their species. The implications of these discoveries are discussed in terms of agricultural pests. Bangladesh J. Zool. 46(2): 217-230, 2018